Karakteristik Rumput Banto (Leersia hexandra Sw.) Berdasarkan Makroskopik dan Mikroskopik - Wa Ode Rungaya Ningsih Komala; Nur Mita; Yurika Sastyarina (Proceeding of Mulawarman Pharmaceuticals Conferences, 2020)
Banto (Leersia hexandra Sw.) is a weed that is often used as animal feed, which is used to remove toxins in the body. The research to study the characteristics of Banto macroscopically and microscopically. A macroscopic test were carried out directly on the physical properties of Banto. Then a microscopic test of Bantos powder simplicia was conducted using a microscope. The result of the macroscopic examination of Banto show that Banto has smooth stem segments, roots on the stem segments, height can reach 1 m, leaf width reaches 0,4 cm-1 cm, leaf length is 5 cm-23 cm, the sides are rough and have sharp edges. For the results of the microscopic examination of fresh grass at 40× magnification and 100× magnification showed the presence of epidermis, stomata, and chlorophyll. The result of microscopic study of Banto simplicia at 40× magnification and 100× magnification showed the presence of epidermis and chlorophyll.